Preparation method and application of cotton fabric based oil-water separation membrane

By functionalizing the cotton fabric with dopamine and potassium permanganate solution and further processing in silanol and propylene monomer solutions, a cotton fabric-based oil-water separation film with excellent oil-water separation performance and ion adsorption ability was prepared, solving the problems of oil-water separation and ion adsorption in the prior art, and achieving efficient and economical oil-water separation and ion adsorption effects.

CN119838442AActive Publication Date: 2025-04-18ZHEJIANG OCEAN UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510313140.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-18
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The existing oil-water separation membranes are difficult to meet the needs of high water content oil-water separation and ion adsorption and detachment in the oil and gas mining industry, and there are problems such as unsatisfactory performance, difficult to obtain raw materials or high costs.

Method used

By placing the cotton fabric in dopamine and potassium permanganate solution for functionalization, an amine-manganese-based cotton fabric was formed, and further treated in silanol and propylene monomer solutions, a cotton fabric-based oil-water separation film with excellent oil-water separation performance and ion adsorption capacity was prepared.

Benefits of technology

It has achieved improvement in oil-water separation performance, good stability, friction resistance, acid and alkali resistance, and can effectively adsorb and remove lithium ions, with low cost and easy access to raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a cotton fabric based oil-water separation membrane, and belongs to the technical field of separation and adsorption of oil-water separation membranes. The preparation method of the cotton fabric-based oil-water separation membrane comprises the following steps: firstly, sequentially immersing a cotton fabric into a dopamine solution and a potassium permanganate solution for reaction, and drying to obtain an amine manganese-based cotton fabric; then immersing the amine manganese-based cotton fabric into a silanol solution, putting the amine manganese-based cotton fabric into a closed container filled with ammonia gas for reaction, then immersing the amine manganese-based cotton fabric into a propylene monomer solution for reaction under a vacuum condition, and cleaning and drying to obtain the cotton fabric-based oil-water separation membrane. The prepared cotton fabric based oil-water separation membrane is excellent in oil-water separation performance and low in cost, the separation efficiency reaches 99% or above, the oil-water separation problem of by-products in oil and gas exploitation can be solved, and lithium ions can be adsorbed and removed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil-water separation membrane separation and adsorption, in particular to a preparation method and application of a cotton fabric-based oil-water separation membrane. Background Art

[0002] In the field of industrial production, especially in the oil and gas extraction industry, oil-water separation is a vital and extremely challenging task. With the continuous exploitation of oil and gas resources, a large number of by-products containing oil-water mixtures will be produced, some of which have a water content of even greater than 95%. The efficient and accurate separation of these oil-water mixtures is not only related to the effective recycling of resources, but also involves many subsequent environmental protection treatments. At the same time, under the needs of many industrial application scenarios and environmental governance, there is also an urgent need for functional materials that can effectively adsorb and remove specific ions. Although some existing oil-water separation membranes can achieve the oil-water separation function to a certain extent, they often have problems such as unsatisfactory performance, difficult to obtain raw materials, or high costs. It is difficult to simultaneously meet the actual needs of oil-water separation and ion adsorption and removal of high-water-content by-products in the oil and gas extraction industry. In the prior art, a Chinese invention patent with publication number CN116510523A discloses a method for preparing a corrosion-resistant nitrocellulose cotton fabric oil-water separation filter membrane and its application. The separation filter membrane uses cotton fabric as a raw material, is boiled in a sodium hypochlorite solution, washed with ethanol and deionized water respectively and dried at room temperature, and then immersed in a nitrocellulose solution and dried at room temperature. A Chinese invention patent with publication number CN110526337A discloses a method for preparing an oil-water separation membrane, which uses a solution-gel method to construct a SiO2 microsphere structure on cotton fabric to obtain a cotton fabric loaded with silica microspheres, and thiophene is formed into polythiophene and coated on the surface of the cotton fabric loaded with silica microspheres by a solid phase coupling method. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation method and application of a cotton fabric-based oil-water separation membrane.

[0004] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A method for preparing a cotton fabric-based oil-water separation membrane comprises: placing cotton fabric in a functional solution and performing functional treatment to prepare the cotton fabric-based oil-water separation membrane; the functional solution comprises at least a dopamine solution and a potassium permanganate solution, the concentration of the dopamine solution is 1-10 g / L, and the concentration of the potassium permanganate solution is 0.01-0.1 mol / L; Preferably, in the functionalization treatment, the cotton fabric is first immersed in a dopamine solution for treatment, and then immersed in a potassium permanganate solution for treatment to obtain an amine manganese-based cotton fabric, that is, a cotton fabric-based oil-water separation membrane. When the dopamine solution is used to treat the cotton fabric, dopamine undergoes a self-polymerization reaction to form a polydopamine layer rich in phenolic hydroxyl groups and amine groups on the surface of the cotton fabric. Subsequently, manganese dioxide is formed by treatment with a potassium permanganate solution. This functionalization treatment can also transform the cotton fabric into a cotton fabric-based oil-water separation membrane, which can effectively achieve oil-water separation and has good stability.

[0005] Preferably, the mass ratio of the cotton fabric to the dopamine solution is 1:50-100; the mass ratio of the cotton fabric to the potassium permanganate solution is 1:50-100.

[0006] Preferably, the functional solution also includes a silanol solution, which includes ethanol, tetraethyl orthosilicate, mercaptopropyl triethoxysilane and 3-aminopropyl trimethoxysilane; the mass ratio of ethanol to tetraethyl orthosilicate is 1-8:1-4, the mass ratio of ethanol to mercaptopropyl triethoxysilane is 1-8:2-5, and the mass ratio of ethanol to 3-aminopropyl trimethoxysilane is 1-8:1-2.

[0007] Preferably, the functional solution further comprises an propylene monomer solution, wherein the propylene monomer solution comprises ethanol, N-phenylacrylamide, acryloxytrimethylsilane and azobisisobutyronitrile; the concentration of N-phenylacrylamide is 0.05-0.5 mol / L, the concentration of acryloxytrimethylsilane is 0.05-0.5 mol / L, and the amount of azobisisobutyronitrile is 1-5 wt% relative to the total mass of N-phenylacrylamide and acryloxytrimethylsilane. Under the action of azobisisobutyronitrile, N-phenylacrylamide and acryloxytrimethylsilane can undergo free radical polymerization, that is, the acryl groups in N-phenylacrylamide and acryloxytrimethylsilane polymerize with the thiol groups on the silica structure on the surface of the cotton fabric to form a propylene polymer, thereby improving the oil-water separation efficiency of the cotton fabric-based oil-water separation membrane, and the oil-water separation efficiency remains good after friction or acid-base action.

[0008] Preferably, the functionalization treatment further comprises immersing the amine manganese-based cotton fabric in a silanol solution for treatment, and the amine manganese-based cotton fabric is treated in the silanol solution to obtain a silica-based cotton fabric.

[0009] Preferably, the functionalization treatment further comprises immersing the silica-based cotton fabric in a propylene monomer solution to obtain a functional layer-based cotton fabric, namely, a cotton fabric-based oil-water separation membrane.

[0010] Preferably, the amine manganese-based cotton fabric is immersed in the silanol solution and stirred at 50-80°C for 1-5 hours; then placed in a sealed container filled with ammonia gas and reacted at 30-60°C for 20-60 minutes.

[0011] Preferably, the silica-based cotton fabric is immersed in a propylene monomer solution and reacted at 60-80° C. under vacuum conditions for 12-24 h.

[0012] Preferably, the cotton fabric is first immersed in a dopamine solution and reacted on a shaking table at a rotation speed of 100-300 rpm for 12-36 hours; and then immersed in a potassium permanganate solution and reacted at 60-80° C. for 6-10 hours.

[0013] The invention discloses a cotton fabric-based oil-water separation membrane prepared by the method.

[0014] The invention discloses application of the cotton fabric-based oil-water separation membrane in oil and gas production.

[0015] The invention discloses a method for preparing a cotton fabric-based oil-water separation membrane, comprising: immersing the cotton fabric in a dopamine solution, reacting on a shaking table at a rotation speed of 100-300 rpm for 12-36 h, then immersing the cotton fabric in a potassium permanganate solution, reacting at 60-80°C for 6-10 h, and drying at 50-70°C to obtain an amine manganese-based cotton fabric, namely, the cotton fabric-based oil-water separation membrane.

[0016] Preferably, the concentration of dopamine solution is 1-10 g / L, and the mass ratio of cotton fabric to dopamine solution is 1:50-100; the concentration of potassium permanganate solution is 0.01-0.1 mol / L, and the mass ratio of cotton fabric to potassium permanganate solution is 1:50-100.

[0017] The invention discloses a method for preparing a cotton fabric-based oil-water separation membrane, which comprises two steps of pretreating the cotton fabric and preparing the cotton fabric-based oil-water separation membrane.

[0018] Preferably, in the pretreatment of cotton fabric, the cotton fabric is immersed in a dopamine solution, reacted on a shaking table at a rotation speed of 100-300 rpm for 12-36 h, then immersed in a potassium permanganate solution with a concentration of 1.5, reacted at 60-80 ° C for 6-10 h, and dried at 50-70 ° C to obtain amine manganese-based cotton fabric.

[0019] Preferably, the concentration of the dopamine solution is 1-10 g / L, the mass ratio of the cotton fabric to the dopamine solution is 1:50-100, the concentration of the potassium permanganate solution is 0.01-0.1 mol / L, and the mass ratio of the cotton fabric to the potassium permanganate solution is 1:50-100.

[0020] Preferably, in the preparation of the cotton fabric-based oil-water separation membrane, the amine manganese-based cotton fabric is immersed in a silanol solution, stirred at 50-80°C for 1-5 hours, and then placed in a sealed container filled with ammonia gas, and reacted at 30-60°C for 20-60 minutes to obtain a silica-based cotton fabric. The silica-based cotton fabric is taken out and immersed in a propylene monomer solution, and reacted at 60-80°C under vacuum conditions for 12-24 hours, washed with ethanol and deionized water in turn, and dried at 60-80°C to obtain a functional layer cotton fabric, that is, a cotton fabric-based oil-water separation membrane.

[0021] Preferably, the silanol solution is composed of ethanol, tetraethyl orthosilicate, mercaptopropyl triethoxysilane and 3-aminopropyl trimethoxysilane, the mass ratio of ethanol to tetraethyl orthosilicate is 1-8:1-4, the mass ratio of ethanol to mercaptopropyl triethoxysilane is 1-8:2-5, and the mass ratio of ethanol to 3-aminopropyl trimethoxysilane is 1-8:1-2. The mass ratio of the amount of amine manganese-based cotton fabric used to the silanol solution is 1-10:80-160.

[0022] Preferably, the propylene monomer solution is composed of ethanol, N-phenylacrylamide, acryloxytrimethylsilane and azobisisobutyronitrile, the concentration of N-phenylacrylamide is 0.05-0.5 mol / L, the concentration of acryloxytrimethylsilane is 0.05-0.5 mol / L, and the amount of azobisisobutyronitrile is 1-5 wt% relative to the total mass of N-phenylacrylamide and acryloxytrimethylsilane.

[0023] More preferably, when amine manganese-based cotton fabric is immersed in a silanol solution, 1,5-benzyl pentane is added, and the mass ratio of the amount of amine manganese-based cotton fabric used to the amount of 1,5-benzyl pentane is 1-5:20-40. The addition of 1,5-benzyl pentane can be grafted onto the surface of silica and introduce new groups, which work together with N-phenylacrylamide and acryloxytrimethylsilane to form an propylene-based polymer, thereby further improving the performance of the cotton fabric-based oil-water separation membrane.

[0024] The present invention performs functional treatment on cotton fabric, that is, the cotton fabric is first immersed in dopamine solution and potassium permanganate solution in sequence for reaction and drying, then immersed in silanol solution, placed in a closed container filled with ammonia for reaction, and then immersed in propylene monomer solution for reaction under vacuum conditions, and a cotton fabric-based oil-water separation membrane is obtained after cleaning and drying. Therefore, it has the following beneficial effects: excellent oil-water separation performance, friction resistance, acid and alkali resistance, wide source of raw materials and low cost, and can also adsorb and remove lithium ions while separating oil and water. Therefore, the purpose of the present invention is to provide a method for preparing a cotton fabric-based oil-water separation membrane with excellent performance, easy availability and low cost, so as to solve the oil-water separation problem of by-products in oil and gas production, especially by-products with a water content greater than 95%. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a graph showing the test results of the dynamic adsorption capacity and adsorption efficiency of Li(Ⅰ) by the cotton fabric-based oil-water separation membrane in Example 1.

[0026] Figure 2 This is a graph showing the test results of the desorption rate of Li(Ⅰ) of the cotton fabric-based oil-water separation membrane in Example 1.

[0027] Figure 3 This is the test result of abrasion stability of cotton fabric-based oil-water separation membrane.

[0028] Figure 4 This is the acid and alkali stability test result of cotton fabric-based oil-water separation membrane. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.

[0031] Example 1 5 g of cotton fabric was immersed in 100 g of 2 g / L dopamine solution, shaken at 150 rpm for 24 h, then immersed in 100 g of 0.05 mol / L potassium permanganate solution, reacted at 80 ℃ for 8 h, and dried at 60 ℃ to obtain amine manganese-based cotton fabric, i.e., cotton fabric-based oil-water separation membrane.

[0032] Example 2 5 g of cotton fabric was immersed in 100 g of 2 g / L dopamine solution, shaken at 150 rpm for 24 h, then immersed in 100 g of 0.05 mol / L potassium permanganate solution, reacted at 80 ℃ for 8 h, and dried at 60 ℃ to obtain amine manganese-based cotton fabric.

[0033] 5 g of amine manganese-based cotton fabric was immersed in 100 g of silanol solution, stirred at 80 °C for 2 h, and then placed in a sealed container filled with ammonia and reacted at 50 °C for 30 min to obtain silica-based cotton fabric. The silica-based cotton fabric was taken out and immersed in propylene monomer solution, and reacted at 70 °C under vacuum conditions for 18 h, then washed with ethanol and deionized water in turn, and dried at 80 °C to obtain a functional layer cotton fabric, that is, a cotton fabric-based oil-water separation membrane. The silanol solution consists of ethanol, tetraethyl orthosilicate, mercaptopropyl triethoxysilane and 3-aminopropyl trimethoxysilane, the mass ratio of ethanol to tetraethyl orthosilicate is 5:3, the mass ratio of ethanol to mercaptopropyl triethoxysilane is 5:2, and the mass ratio of ethanol to 3-aminopropyl trimethoxysilane is 5:1. The propylene monomer solution is composed of ethanol, N-phenylacrylamide, acryloxytrimethylsilane and azobisisobutyronitrile, the concentration of N-phenylacrylamide is 0.1 mol / L, the concentration of acryloxytrimethylsilane is 0.1 mol / L, and the amount of azobisisobutyronitrile is 2 wt% relative to the total mass of N-phenylacrylamide and acryloxytrimethylsilane.

[0034] Example 3 The difference between this embodiment and embodiment 2 is that the concentration of N-phenylacrylamide in the propylene monomer solution is 0.2 mol / L, the concentration of acryloxytrimethylsilane is 0.2 mol / L, and the rest is the same as embodiment 2.

[0035] Example 4 5 g of cotton fabric was immersed in 100 g of 2 g / L dopamine solution, shaken at 150 rpm for 24 h, then immersed in 100 g of 0.05 mol / L potassium permanganate solution, reacted at 80 ℃ for 8 h, and dried at 60 ℃ to obtain amine manganese-based cotton fabric.

[0036] 5 g of amine manganese-based cotton fabric was immersed in 100 g of silanol solution, 0.25 g of 1,5-pentanedioic acid monobenzyl ester was added, stirred at 80 ° C for 2 h, and then placed in a sealed container filled with ammonia and reacted at 50 ° C for 30 min to obtain silica-based cotton fabric. The silica-based cotton fabric was taken out and immersed in propylene monomer solution, and reacted at 70 ° C under vacuum conditions for 18 h, then washed with ethanol and deionized water in turn, and dried at 80 ° C to obtain a functional layer cotton fabric, that is, a cotton fabric-based oil-water separation membrane. The silanol solution consists of ethanol, tetraethyl orthosilicate, mercaptopropyl triethoxysilane and 3-aminopropyl trimethoxysilane, the mass ratio of ethanol to tetraethyl orthosilicate is 5:3, the mass ratio of ethanol to mercaptopropyl triethoxysilane is 5:2, and the mass ratio of ethanol to 3-aminopropyl trimethoxysilane is 5:1. The propylene monomer solution is composed of ethanol, N-phenylacrylamide, acryloxytrimethylsilane and azobisisobutyronitrile, the concentration of N-phenylacrylamide is 0.1 mol / L, the concentration of acryloxytrimethylsilane is 0.1 mol / L, and the amount of azobisisobutyronitrile is 2 wt% relative to the total mass of N-phenylacrylamide and acryloxytrimethylsilane.

[0037] Example 5 The difference between this embodiment and embodiment 4 is that when the amine manganese-based cotton fabric is immersed in the silanol solution, the weight of 1,5-pentanedioic acid monobenzyl ester added is 0.125 g, and the rest is the same as embodiment 4.

[0038] Comparative Example 1 The difference between this comparative example and Example 2 is that the propylene monomer solution does not contain acryloxytrimethylsilane, and the rest is the same as Example 2.

[0039] Comparative Example 2 The difference between this comparative example and Example 2 is that the propylene monomer solution does not contain N-phenylacryloyl, and the rest is the same as Example 2.

[0040] Comparative Example 3 The difference between this comparative example and Example 4 is that the propylene monomer solution does not contain acryloyloxytrimethylsilane and N-phenylacryloyl. Others are the same as Example 4.

[0041] Li(I) dynamic adsorption capacity and adsorption efficiency test Effect of separation times on dynamic adsorption amount and adsorption efficiency of Li(I): Under 25 ℃, a lithium chloride solution with a concentration of 35 mg / L was mixed with n-hexane in a volume ratio of 7:3, and the cotton fabric-based oil-water separation membrane of Example 1 was used as the separation membrane. The mixture was poured into a container on the membrane for filtration, and a beaker was placed under the membrane to receive the liquid passing through the membrane. A total of ten oil-water separation experiments were performed. The calculation formula of the dynamic adsorption amount is: Q=(C0-C) / m, where C0 is the initial content of Li(I), C is the content of Li(I) in the cotton fabric-based oil-water separation membrane after each oil-water separation experiment or reaching a certain time and temperature, and m is the mass of the cotton fabric-based oil-water separation membrane. The calculation formula of the adsorption efficiency is: E=Q / Q0×100%, where Q is the adsorption amount of Li(I) in the cotton fabric-based oil-water separation membrane after each oil-water separation experiment, and Q0 is the initial content of Li(I).

[0042] Effect of separation time and temperature on the adsorption amount of Li(I): 100 mL of 100 mg / L lithium chloride solution and 0.4 g of the cotton fabric-based oil-water separation membrane of Example 1 were placed in a beaker, and the changes in the adsorption amount over time or temperature were observed and recorded in a shaking table.

[0043] The results of Li(I) dynamic adsorption and adsorption efficiency tests are shown in Figure 1 As shown, Figure 1 (a) is the effect of separation times on the adsorption amount, Figure 1 (b) is the effect of separation times on adsorption efficiency, Figure 1 (c) is the effect of separation time on the adsorption amount, Figure 1 (d) is the effect of separation temperature on the adsorption amount. It can be seen that during the oil-water separation process, the adsorption amount of Li(Ⅰ) by the cotton fabric-based oil-water separation membrane of Example 1 gradually increased. After completing the tenth oil-water separation experiment, the cumulative adsorption amount reached 10.25 mg / g, which shows that the cotton fabric-based oil-water separation membrane of Example 1 has a good Li(Ⅰ) adsorption capacity; on the contrary, the adsorption efficiency of Li(Ⅰ) gradually decreased with the increase of separation times, from the initial 82% to 38.9%, a decrease of about 43.1%, which shows that after repeated use of the cotton fabric-based oil-water separation membrane, the Li(Ⅰ) adsorption efficiency of the membrane will be reduced; it can also be seen that with the passage of time, the adsorption amount of Li(Ⅰ) by the cotton fabric-based oil-water separation membrane of Example 1 showed an upward trend, and the adsorption amount basically tended to be stable at 60 minutes, reaching the adsorption equilibrium state, and the adsorption equilibrium amount at this time was 7.85 mg / g; it can also be seen that with the gradual increase of temperature, the initial adsorption amount of Li(Ⅰ) increased, but after the temperature exceeded 45 °C, the adsorption amount began to show a downward trend, from the previous 8.2 mg / g to 5.46 mg / g, the decrease was 33.41%, which shows that cotton fabric-based oil-water separation membrane is more suitable for use when the ambient temperature is below 45 ℃.

[0044] Li(Ⅰ) desorption rate test The cotton fabric-based oil-water separation membrane of Example 1 was eluted with 0.04 mol / L sulfuric acid solution at a rate of 20 mL / min. The cotton fabric-based oil-water separation membrane contained 10.2 mg / g Li(Ⅰ) and the elution time was 120 s. The calculation formula of Li(Ⅰ) desorption rate is: Ae=(C0-C t ) / C0×100%, where C0 is the initial Li(Ⅰ) content in the cotton fabric-based oil-water separation membrane, C t is the content of residual Li(Ⅰ) in the cotton fabric-based oil-water separation membrane at the elution time of .

[0045] The test results of Li(Ⅰ) desorption rate are as follows Figure 2 As shown in the figure, it can be seen that during the continuous elution of 120 s, the desorption rate of Li(Ⅰ) gradually increased and reached 95% at 120 s. This shows that Li(Ⅰ) adsorbed by the cotton fabric-based oil-water separation membrane can be eluted by the sulfuric acid solution, and the desorption time is short, which is conducive to the recovery of Li(Ⅰ).

[0046] Wear stability test The friction test was carried out to compare the oil-water separation efficiency before and after the test, and to evaluate the friction stability of the cotton fabric-based oil-water separation membrane. The friction test was to place the cotton fabric-based oil-water separation membrane and a 50 g weight on a 500-mesh sandpaper in turn, drag the sandpaper forward about 20 cm in one direction, and repeat it 3 times. The oil-water separation efficiency used a mixed solution of dichloromethane and water as an oil-water mixing model, with the proportion of water being 95 wt%. Dichloromethane was dyed with Sudan red, and water was dyed with methylene blue. The cotton fabric-based oil-water separation membrane was used as a separation membrane, and the oil-water mixture was poured into the container on the membrane for filtration. There was another beaker under the membrane to receive the liquid passing through the membrane. The mass of the oil before and after separation was recorded, and the separation efficiency was calculated. The calculation formula for the separation efficiency is: R=(m0 / m1)×100%, where m0 is the mass of the oil after separation and m1 is the mass of the oil before separation. The performance retention rate is calculated as follows: P = R2 / R1 × 100%, where R1 is the oil-water separation efficiency of the cotton fabric-based oil-water separation membrane before the friction resistance test, and R2 is the oil-water separation efficiency of the cotton fabric-based oil-water separation membrane after the friction resistance test.

[0047] The results of the wear stability test are as follows: Figure 3As shown, it can be seen that the cotton fabric-based oil-water separation membrane of the embodiment maintains good performance after the friction resistance test, and the performance retention rate is high, indicating high wear resistance stability; it can also be seen that the performance retention rate of the cotton fabric-based oil-water separation membrane of Example 2 and Example 3 is higher than that of Example 1, which indicates that the propylene group introduced into N-phenylacrylamide and acryloyloxytrimethylsilane can undergo polymerization reaction with the thiol group on the silica structure on the surface of the cotton fabric to form a propylene polymer, thereby enhancing the wear resistance stability and improving the performance retention rate of the cotton fabric-based oil-water separation membrane; it can also be seen that the performance retention rate of the cotton fabric-based oil-water separation membrane of Example 2 is higher than that of Example 3, which indicates that the amount of N-phenylacrylamide and acryloyloxytrimethylsilane used in the propylene monomer solution is not the higher the performance retention; it can also be seen that the performance retention rate of the cotton fabric-based oil-water separation membrane of Example 4 and Example 5 is higher than that of Example 2, which indicates that the addition of 1,5-pentanedioic acid monobenzyl ester when immersed in the silanol solution can modify the silica structure on the surface of the cotton fabric, increase the cotton The surface roughness of the fabric-based oil-water separation membrane is improved, and the performance retention rate is improved; it can also be seen that the performance retention rate of the cotton fabric-based oil-water separation membrane in Example 4 is higher than that in Example 5, which shows that adding an appropriate amount of 1,5-pentanedioic acid monobenzyl ester can improve the performance retention rate of the cotton fabric-based oil-water separation membrane; it can also be seen that the performance retention rate of the cotton fabric-based oil-water separation membrane in Example 2 is higher than that of Comparative Example 1 and Comparative Example 2, which shows that the surface of the cotton fabric-based oil-water separation membrane introduces a propylene polymer formed by polymerization of N-phenylacrylamide and acryloxytrimethylsilane with the thiol group on the surface silica structure, and the performance retention rate is higher than that of a single substance introduced to the surface to form a propylene polymer; it can also be seen that the performance retention rate of the cotton fabric-based oil-water separation membrane in Example 4 is higher than that of Comparative Example 3, which shows that the effect of introducing 1,5-pentanedioic acid monobenzyl ester to modify the silica surface on the surface of the cotton fabric-based oil-water separation membrane on the performance retention rate is lower than the effect of introducing N-phenylacrylamide, acryloxytrimethylsilane and 1,5-pentanedioic acid monobenzyl ester in combination.

[0048] Acid and alkali stability test Acid and alkali resistance test was carried out, and the oil-water separation efficiency before and after the test was compared to evaluate the acid and alkali resistance stability of the cotton fabric-based oil-water separation membrane. The cotton fabric-based oil-water separation membrane of the embodiment was soaked in a hydrochloric acid solution with a pH of 3 and a sodium hydroxide solution with a pH of 11 for 12 h. The performance retention rate was calculated as follows: P = R2 / R1 × 100%, where R1 is the oil-water separation efficiency of the cotton fabric-based oil-water separation membrane before the acid and alkali resistance test, and R2 is the oil-water separation efficiency of the cotton fabric-based oil-water separation membrane after the acid and alkali resistance test.

[0049] Acid and alkali stability test results are as follows Figure 4As shown. It can be seen that the cotton fabric-based oil-water separation membrane of the embodiment maintains good performance after the acid and alkali resistance test, and the performance retention rate is high, indicating that the acid and alkali resistance stability is good; it can also be seen that the performance retention rate of the cotton fabric-based oil-water separation membrane of Example 2 and Example 3 is higher than that of Example 1, which indicates that the propylene group introduced into N-phenylacrylamide and acryloxytrimethylsilane can react with the thiol group on the silica structure on the surface of the cotton fabric to form a propylene polymer, thereby improving the performance retention rate of the cotton fabric-based oil-water separation membrane; it can also be seen that the performance retention rate of the cotton fabric-based oil-water separation membrane of Example 2 is higher than that of Example 3, which indicates that the more the amount of N-phenylacrylamide and acryloxytrimethylsilane used in the propylene monomer solution, the higher the performance retention rate; it can also be seen that the performance retention rate of the cotton fabric-based oil-water separation membrane of Example 4 and Example 5 is higher than that of Example 2, which indicates that 1,5-pentanedioic acid monobenzyl ester is grafted onto the silica surface, and the new group introduced at the same time acts together with the propylene polymer formed by N-phenylacrylamide and acryloxytrimethylsilane, which can The silica structure on the surface is modified to improve the performance retention rate of the cotton fabric-based oil-water separation membrane; it can also be seen that the performance retention rate of the cotton fabric-based oil-water separation membrane in Example 4 is higher than that in Example 5, which shows that adding an appropriate amount of 1,5-pentanedioic acid monobenzyl ester can improve the performance retention rate of the cotton fabric-based oil-water separation membrane; it can also be seen that the performance retention rate of the cotton fabric-based oil-water separation membrane in Example 2 is higher than that of Comparative Example 1 and Comparative Example 2, which shows that the introduction of a propylene polymer formed by the polymerization of N-phenylacrylamide and acryloxytrimethylsilane with the thiol groups on the surface silica structure on the surface of the cotton fabric-based oil-water separation membrane improves the performance retention rate more than the introduction of a single substance to form a propylene polymer on the surface; it can also be seen that the separation efficiency of the cotton fabric-based oil-water separation membrane in Example 4 is higher than that of Comparative Example 3, which shows that the effect of simply introducing 1,5-pentanedioic acid monobenzyl ester to modify the silica surface on the surface of the cotton fabric-based oil-water separation membrane on the performance retention rate is lower than the effect of introducing N-phenylacrylamide, acryloxytrimethylsilane and 1,5-pentanedioic acid monobenzyl ester in combination.

[0050] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.

[0051] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.

Claims

1. A method for preparing a cotton fabric-based oil-water separation membrane, comprising: The cotton fabric is placed in a functional solution and subjected to a functional treatment to prepare a cotton fabric-based oil-water separation membrane; The functional solution at least includes a dopamine solution and a potassium permanganate solution, wherein the concentration of the dopamine solution is 1-10 g / L, and the concentration of the potassium permanganate solution is 0.01-0.1 mol / L; In the functionalization treatment, the cotton fabric is first immersed in a dopamine solution for treatment, and then immersed in a potassium permanganate solution for treatment to obtain an amine manganese-based cotton fabric, that is, a cotton fabric-based oil-water separation membrane.

2. The method for preparing a cotton fabric-based oil-water separation membrane according to claim 1, characterized in that: The mass ratio of the cotton fabric to the dopamine solution is 1:50-100; the mass ratio of the cotton fabric to the potassium permanganate solution is 1:50-100.

3. The method for preparing a cotton fabric-based oil-water separation membrane according to claim 1, characterized in that: The functional solution also includes a silanol solution, which includes ethanol, tetraethyl orthosilicate, mercaptopropyl triethoxysilane and 3-aminopropyl trimethoxysilane; the mass ratio of ethanol to tetraethyl orthosilicate is 1-8:1-4, the mass ratio of ethanol to mercaptopropyl triethoxysilane is 1-8:2-5, and the mass ratio of ethanol to 3-aminopropyl trimethoxysilane is 1-8:1-2.

4. The method for preparing a cotton fabric-based oil-water separation membrane according to claim 1, characterized in that: The functional solution also includes an propylene monomer solution, which includes ethanol, N-phenylacrylamide, acryloxytrimethylsilane and azobisisobutyronitrile; the concentration of N-phenylacrylamide is 0.05-0.5 mol / L, the concentration of acryloxytrimethylsilane is 0.05-0.5 mol / L, and the amount of azobisisobutyronitrile is 1-5 wt% relative to the total mass of N-phenylacrylamide and acryloxytrimethylsilane.

5. The method for preparing a cotton fabric-based oil-water separation membrane according to claim 1, characterized in that: The functionalization treatment also includes immersing the amine manganese-based cotton fabric in a silanol solution for treatment, and the amine manganese-based cotton fabric is treated in the silanol solution to obtain a silica-based cotton fabric.

6. The method for preparing a cotton fabric-based oil-water separation membrane according to claim 5, characterized in that: The functionalization treatment also includes immersing the silica-based cotton fabric in a propylene monomer solution to obtain a functional layer-based cotton fabric, namely a cotton fabric-based oil-water separation membrane.

7. The method for preparing a cotton fabric-based oil-water separation membrane according to claim 5, characterized in that: The amine manganese-based cotton fabric is immersed in a silanol solution and stirred at 50-80°C for 1-5 hours; then placed in a sealed container filled with ammonia gas and reacted at 30-60°C for 20-60 minutes.

8. The method for preparing a cotton fabric-based oil-water separation membrane according to claim 6, characterized in that: The silica-based cotton fabric is immersed in a propylene monomer solution and reacted at 60-80° C. under vacuum conditions for 12-24 hours.

9. The cotton fabric-based oil-water separation membrane prepared by the method according to any one of claims 1 to 8.

10. Use of the cotton fabric-based oil-water separation membrane according to claim 9 in oil and gas production.

Citation Information

Patent Citations

  • Preparation method of oil-water separation film

    CN110526337A

  • Preparation method and application of corrosion-resistant nitrocellulose cotton fabric oil-water separation filter membrane

    CN116510523A

  • Super-hydrophobic flame retardant fabric with function of separating oil from water and preparation method thereof

    CN107724080A

  • Preparation method of durable, efficient and rapid super-hydrophobic oil-water separation cotton fabric

    CN109763316A

  • Method for performing super-hydrophobic modification on waste cotton fabric by dopamine

    CN112323491A